The SmartAG partner: CCAFS East Africa Quarterly Newsletter, January – March 2016 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2016)
We are pleased to share with you the second issue of our quarterly newsletter in 2016. We present key highlights from ongoing research and policy engagement initiatives.